Penguatan Profil Pelajar Pancasila (P5) bagi Siswa SMA Alam Al Ghifari Blitar - Muchson, Mochamad; Kusumaningtyas, Dian; Damayanti, Susi; Alvian, Mohammad; Ni’mah, Elsha Ulfatun (GUYUB: Journal of Community Engagement, 2025)
The Merdeka Curriculum emphasizes flexible learning through three main components: intracurricular learning, co-curricular activities through the Strengthening Pancasila Student Profile Project (P5), and extracurricular activities. P5 is designed as an interdisciplinary learning approach focused on solving real-world problems while serving as a means to achieve the six dimensions of the Pancasila Student Profile. This community service project was carried out through socialization, workshops, and mentoring sessions with students in implementing P5 under the theme "Voice of Democracy," which centered on the student council (OSIS) election process. The outcomes of this project include: (1) a project product in the form of essays on the election process and the election of the OSIS president for the 2024-2025 academic year; (2) the development of a project module and teaching materials to support P5 implementation; (3) the systematic and structured execution of project activities; and (4) an improvement in the dimensions of the Pancasila Student Profile, with 11 students reaching the "developing as expected" category and 12 students reaching the "highly developed" category. The implementation of P5 is expected to internalize the values of the Pancasila Student Profile in students' daily lives, shaping a generation that is characterized by integrity, strong morals, and excellence. This project serves as a strategic step in preparing students to face future challenges with both academic skills and strong character.